Upaya Lembaga Dakwah Kampus As-Salam Iain Pontianak Dalam Membangun Karaker Moderat Para Kadernya - Syahri Harendi; Soma (4, 2024)
The As-Salam campus dakwak institution of IAIN Pontianak or abbreviated as LDK As-Salam is an internal campus organization engaged in the religious field. Engaging in the religious field has the responsibility of being a good role model for students in order to maintain the good name of the IAIN Pontianak campus as an Islamic campus. However, these good intentions are often considered too right-wing by ordinary people and considered immoderate by some individuals. This paper aims to explain the efforts of the campus da'wah organization As-Salam IAIN Pontianak to build the moderate character of its cadres so that the bad sigma about LDK As-Salam disappears. Through the Qualitative method with direct interviews to LDK As-Salam administrators and some of its cadres. Researchers produced results stating that LDK As-Salam's efforts to build the character of its cadres through several routine activities, first, the NGOPI (Ngobrol Perkara Islam) work program, second, holding religious moderation seminars, third, sharing in the month of Ramadan. Abstrak Lembaga dakwak kampus As-Salam IAIN Pontianak atau yang disingkat dengan LDK As-Salam merupakan organisasi internal kampus yang bergerak di bidang keagamaan. Bergerak di bidang keagamaan mempunyai tanggung jawab menjadi suri tauladan yang baik bagi mahasiswa demi menjaga nama baik kampus IAIN Pontianak sebagai kampus Islam. Namun niat baik itu sering kali dianggap terlalu eksream kanan oleh orang yang awam dan dianggap tidak moderat oleh sebagian oknum. Penulisan ini bertujuan memaparkan upaya lembaga dakwah kampus As-Salam IAIN Pontianak membangun karakter moderat kadernya sehingga sigma buruk mengenai LDK As- Salam hilang. Melalui metode Kualitaif dengan wawancara langsung kepada pengurus LDK As- Salam dan beberapa kadernya. Peneliti membuahkan hasil yang menyatakan jika upaya LDK As-Salam membangun karakter para kadernya melalui beberapa kegiatan rutin pertama, Program kerja NGOPI (Ngobrol Perkara Islam), Kedua, Mengadakan seminar moderasi Beragama, Ketiga berbagi di bulan Ramadhan.